Proceedings of The 18th Indonesian Occupational Medicine Update (IOMU) 2026 - Occupational Medicine without Borders: Emerging Risks, Evolving Workforces, and Inclusive Collaboration - (Perhimpunan Kedokteran Okupasi Indonesia / PERDOKI), Indonesian Association of Occupational Medicin (UI Scholars Hub, 2026)
This Supplemental Issue of the Occupational and Environmental Medicine Journal of Indonesia (OEMJI) compiles the scientific abstracts presented at the 18th Indonesian Occupational Medicine Update (IOMU) 2026, convened in Surabaya, Indonesia, from 15 to 17 May 2026. The IOMU has matured into the most prominent annual scientific platform of the Indonesian occupational medicine community, hosted by the Indonesian Association of Occupational Medicine Specialists (Perhimpunan Kedokteran Okupasi Indonesia / PERDOKI). Since its inception, the conference has served as a meeting point where clinicians, academics, industrial hygienists, regulators, employers, and worker representatives gather to translate emerging scientific evidence into preventive practice for the Indonesian workforce. The eighteenth edition reaffirms this tradition while expressly broadening its outlook to reflect a rapidly transforming global landscape. The theme of the 2026 conference,